An Unusual Case of Sebaceous Gland Carcinoma Mimicking Recurrent Chalazion in a Young Patient - Mittal, Parul; Gupta, Saroj; Khan, Manal Mohammad; Priyanka, (Nepalese Journal of Ophthalmology, 2026)
Introduction: Chalazion is a common eyelid lesion usually treated conservatively or with minor surgical interventions,such as incision and curettage or intralesional steroid injections. However, recurrent or atypical chalazion in a youngadult patient warrants further investigation to exclude malignant conditions such as sebaceous gland carcinoma(SGC).Case: Here an unusual case of SGC presenting with a recurrent chalazion in a young adult patient is reported, whichwas diagnosed by a biopsy for histopathological examination.Observation: Histopathology revealed sebaceous gland carcinoma. The patient subsequently underwent wide localexcision of the lesion, followed by oculoplastic reconstruction. Post-operative follow-up over one year revealed norecurrence or metastasis.Conclusion: This case highlights the importance of considering malignancies like sebaceous gland carcinoma inrecurrent or atypical chalazion cases, even in young patients. Early biopsy and histopathological evaluation areessential for timely diagnosis and management to prevent metastasis and ensure better patient outcomes.